Genetic correlation and path analysis of common bean inoculated with Rhizobium tropici and Azospirillum brasilense - Merquides Contardi, Lucymara [UNESP]; Ettore Pavan, Bruno [UNESP]; de Almeida, Patricia [UNESP]; Hiroda Kamano, Igor [UNESP]; Facioli Otoboni, Maria Eduarda [UNESP]; Ferreira de Lima, Sebastião; Dantas Alves, Vitória Carolina; Barros Nunes, Rita de Cássia (My University, 2024)
The interaction between bean (Phaseolus vulgaris L.) genotypes and N-fixing microorganisms has the potential to be utilized in sustainable agricultural production. Thus, the aim of this study was to verify the effects of the interaction for growth, production and nodulation characteristics between the bacteria Rhizobium tropici and Azospirillum brasilense among different bean genotypes. The experiments were conducted in the Selvíria, Mato Grosso do Sul, Brazil, in 2018 and 2019, in randomized block design with three replicates in a 20 × 3 factorial scheme; 20 common bean genotypes were tested under three forms of inoculation (no inoculation, inoculation with R. tropici, co-inoculation of R. tropici + A. brasilense). The number of grains per pod and nodule mass had the most significant direct positive effect on grain yield. For nodulation, a positive correlation of strong magnitude was observed between mass of the aerial part and number of pods per plant (0.68), stem diameter and mass of nodules (0.92) and first pod insertion height and number of nodules (0.64). In the path analysis, the number of grains per pod had the most significant direct effect (0.57) on the grain productivity variable. Regarding nodulation characteristics, selection for nodule mass was preferred due to its direct effect on grain yield as opposed to the number of nodules, which has a negative effect. This suggests an advantage of larger nodules with greater individual mass than a large number of small nodules for both improved yield and N fixing by common bean plants.
Keywords: Biological nitrogen fixation; co-inoculation; growth-promoting bacteria; Phaseolus vulgaris